2021
DOI: 10.22456/1679-9216.116488
|View full text |Cite
|
Sign up to set email alerts
|

True Prevalence and Spatial Distribution of Equine Infectious Anemia Virus (EIAV) in Horses from Northeast Region of Brazil

Abstract: Background: Equine infectious anemia (EIA) is a viral infection, caused by a lentivirus of the Retroviridae family, Orthoretrovirinael subfamily and its occurrence generates significant economic losses due to culling of positive animals as a measure of infection control. The objective of this work was to determine the prevalence of horses positive for equine infectious anemia virus (EIAV) and to identify the occurrence of areas with higher densities of cases in the states of Paraíba (PB), Pernambuco (PE), Rio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The seroprevalence results found in horses (17.45%, 85 out of 487 serum samples) using AGID agree with those of Márquez-Alvarado et al (2015) who reported low prevalence values (4%) in creole horses from Venezuela. Antibodies against EIAV antigens diagnosed by cELISA in horses (15.40%, 75 out of 487 serum samples) were higher than those in Venezuela (10.2%, creole horses) and the northeast region of Brazil during subsequent dry periods of 2017 (1.22%) and 2018 (1.32%) (Bezerra et al, 2021;Márquez-Alvarado et al, 2015). The AGID test has high specificity and has become established as the gold standard for serological diagnosis of EIA.…”
Section: Resultsmentioning
confidence: 93%
“…The seroprevalence results found in horses (17.45%, 85 out of 487 serum samples) using AGID agree with those of Márquez-Alvarado et al (2015) who reported low prevalence values (4%) in creole horses from Venezuela. Antibodies against EIAV antigens diagnosed by cELISA in horses (15.40%, 75 out of 487 serum samples) were higher than those in Venezuela (10.2%, creole horses) and the northeast region of Brazil during subsequent dry periods of 2017 (1.22%) and 2018 (1.32%) (Bezerra et al, 2021;Márquez-Alvarado et al, 2015). The AGID test has high specificity and has become established as the gold standard for serological diagnosis of EIA.…”
Section: Resultsmentioning
confidence: 93%